PENGARUH PERMAINAN DALAM METODE FUNDAMENTAL MOTOR SKILL TERHADAP PENINGKATAN GERAK DASAR PADA ANAK TUNAGRAHITA RINGAN DI SLB-C TUNAS HARAPAN KARAWANG - Falah Fadhlurrahnman Khalil; Akhmad Dimyati; Tedi Purbangkara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to determine the effect of games in the Fundamental Motor Skill on the improvement of basic movements in children with mild tunagrahita SLB-C Tunas Harapan Karawang. The method used is experimental with a quantitative approach. The study population consisted of 20 grade 3 students, who were taken using puposive sampling technique. This research design uses Pre-Experiment with One-Group Pretest-Posttest model. The instrument used for data collection is a basic motion test, with a mean pretest value of 20.64 and a mean posttest value of 25.65, Hypothesis testing using Paired Sample t-test gives a significance value (2-tailed) of 0.001 < 0.005, indicating a significant influence between the values before and after treatment. Thus, it can be concluded that the fundamental motor skill method has a positive influence on improving basic movements in activity activities at SLB-C Tunas Harapan Karawang.